STRATEGI MEWUJUDKAN SUATU ORGANISASI PEMBELAJAR - Dingot Hamonangan Ismail (POLITEKNIK LP3I JAKARTA, 2016)
The era of globalization requires HR organizations or companies who have extensive knowledge and insight as well as a reliable competence. With knowledge (breadth) and reliable competencies, organizations can survive in a highly competitive life by producing superior works and provide benefits to the lives of others. The best container for growing a superior human resources is the presence of a learning organization- organizations that continuously develops its ability, to create the future.Keywords: Globalization, Human Resource Management, Organizational Learning